A CONCEPTUAL FRAMEWORK ON THE IMPLEMENTATION OF ACCRUAL ACCOUNTING - khoirul aswar (Jurnal Studi Akuntansi Pajak Keuangan, 2024)
An issue in Mandailing Natal District about financial statement disclosure makes government needs to implement accrual accounting in accordance with government accounting standards. This research investigates how the local government of Mandailing Natal regency has made disclosures in its financial statements in accordance with applicable accrual accounting. The research aims to determine the effect of training and communication support toward the accrual accounting implementation. This research contributes in the form of input to local governments in implementing policies on Government Accounting Standards (PP No. 71 of 2010) and provides input to improve the quality of human resources in implementing accrual accounting.